Signaling LTPs: A new plant LTPs sub-family? - Pii, Youry (Plant Signal Behav, 2010)
Numerous plant non specific Lipid Transfer Protein (nsLTPs) have been characterized for their antimicrobial activity, suggesting for these proteins a direct role in the protection against pathogenic microorganisms. Another group of LTPs seems to be involved in structural events in the extracellular matrix through binding and transport of hydrophobic molecules. More recently, some LTPs putatively involved in the symbiotic interaction between legumes and rhizobia have been identified. We investigated the role of MtN5, a LTP from Medicago truncatula, which is specifically expressed in the roots and induced by both Sinorhizobium meliloti and a root pathogenic fungus. Once the symbiosis has been established, MtN5 is preferentially accumulated in the root nodule. The suppression of MtN5 transcript, obtained by means of an RNAi approach, resulted in a reduced nodulation, whereas its overexpression led to an increased number of nodules produced by S. meliloti. These observations demonstrated that MtN5 is required for an efficient nodulation. On the basis of the amino acid sequence, MtN5 has been included in the nsLTP-like sub-family, together with Arabidopsis thaliana DIR1, a protein playing a role in SAR signaling. The putative role(s) for this LTP in the symbiotic association are discussed in the present commentary. MtN5, together with DIR1 and other new LTPs, are proposed to form a new LTP subfamily involved in lipid signalling.